1984
DOI: 10.1002/art.1780270307
|View full text |Cite
|
Sign up to set email alerts
|

Polymyositis/dermatomyositis and pregnancy

Abstract: Eighteen women with polymyositis/dermatomyositis (PM/DM) were studied to determine the possible influences of pregnancy on the disease and the influence of the disease on pregnancy. Before the onset of PM/DM there were 77 pregnancies: 7 (9%) ended in abortion, 2 (2.5%) in perinatal deaths, with a total fetal loss of 11.5%. There were 3 (3.8%) premature newborns that survived. These figures are equivalent to those of the general population. There were 10 pregnancies in 7 patients coinciding with PM/DM, 1 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
9

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 11 publications
3
36
1
9
Order By: Relevance
“…It is evident, therefore, that women in the reproductive age group are somewhat spared from the disease, and there is relatively little infor mation concerning the outcome of pregnancy in patients with DM, compared with other connective tissue diseases including rheumatoid arthritis and systemic lupus erythe matosus [2,4]. In contrast with previous reports on increased incidence of exacerbation throughout preg nancy and puerperium [5][6][7][8][9][10], the patients described below introduced 2 cases of successful outcomes of preg nancy complicated with DM.…”
contrasting
confidence: 48%
“…It is evident, therefore, that women in the reproductive age group are somewhat spared from the disease, and there is relatively little infor mation concerning the outcome of pregnancy in patients with DM, compared with other connective tissue diseases including rheumatoid arthritis and systemic lupus erythe matosus [2,4]. In contrast with previous reports on increased incidence of exacerbation throughout preg nancy and puerperium [5][6][7][8][9][10], the patients described below introduced 2 cases of successful outcomes of preg nancy complicated with DM.…”
contrasting
confidence: 48%
“…As taxas de fertilidade da DM ou PM podem estar diminuídas. A redução da função gonadal ovariana pode ocorrer pela própria atividade da doença crônica e/ou uso dos imussupressores (15) . Por sua vez, King e Chow (7) reportaram uma incidência de mulheres nulíparas de 12% em 78 pacientes com DM/PM; esses dados foram semelhantes aos encontrados na população geral.…”
Section: Discussionunclassified
“…Both reports looked at very small groups of patients who developed IIM before or during their childbearing years. One concluded that there was an incidence of nulliparity comparable to the general population [ 2 ] while the other concluded that there was a reduction in the fertility rate [ 3 ]. The small sample sizes make it impossible to have confi dence in either conclusion.…”
Section: Fertility In Women With Infl Ammatory Myopathiesmentioning
confidence: 97%